2012
DOI: 10.1016/j.freeradbiomed.2012.02.008
|View full text |Cite
|
Sign up to set email alerts
|

Silybin combined with phosphatidylcholine and vitamin E in patients with nonalcoholic fatty liver disease: A randomized controlled trial

Abstract: The only currently recommended treatment for nonalcoholic fatty liver disease (NAFLD) is lifestyle modification. Preliminary studies of silybin showed beneficial effects on liver function. Realsil (RA) comprises the silybin phytosome complex (silybin plus phosphatidylcholine) coformulated with vitamin E. We report on a multicenter, phase III, double-blind clinical trial to assess RA in patients with histologically documented NAFLD. Patients were randomized 1:1 to RA or placebo (P) orally twice daily for 12 mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
147
0
6

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 214 publications
(160 citation statements)
references
References 60 publications
4
147
0
6
Order By: Relevance
“…A preparation with the name of Realsil (RA) which comprises the silybin phytosome complex (silybin plus phosphatidylcholine) co-formulated with vitamin E was tested. Treatment for 12 months was associated with improvement in liver enzymes, insulin resistance, and liver histology, without increases in body weight (Loguercio et al, 2012).…”
Section: Importance Of and Emphasis On Controlled Clinical Trials On mentioning
confidence: 92%
See 1 more Smart Citation
“…A preparation with the name of Realsil (RA) which comprises the silybin phytosome complex (silybin plus phosphatidylcholine) co-formulated with vitamin E was tested. Treatment for 12 months was associated with improvement in liver enzymes, insulin resistance, and liver histology, without increases in body weight (Loguercio et al, 2012).…”
Section: Importance Of and Emphasis On Controlled Clinical Trials On mentioning
confidence: 92%
“…Silibinin was also reported to improve hepatic oxidative stress and inflammation through the c-Jun NH2-terminal kinase (Salamone et al, 2012a) and nuclear factor kappa B (NF-kB) (Salamone et al, 2012b) pathways. In a clinical trial, silibinin given for 12 months in combination with vitamin E and phosphatidylcholine improved hepatic enzymes and insulin resistance in NAFLD patients (Loguercio et al, 2012). The anti-inflammatory, immunemodulating activity, antifibrotic, and antioxidant effects of silymarin that contribute to its hepatoprotective effect are summarized in a review by Abenavoli et al (2010).…”
Section: In Vitro and In Vivo Experimental Hepatotoxic Models In Livementioning
confidence: 99%
“…Moreover, some studies showed a positive effect of silybin on fibrosis and oxidation [116,117] . In a recent large multicenter RCT, a combination of silybin, vitamin E and phosphatidylcholine reduced hepatic damage and IR [118] . L-carnitine, an endogenous substance precursor of carnitine-palmitoyltransferase 1, is involved in the mitochondrial β-oxidation that affects mitochondrial function.…”
Section: Other Anti-oxidant Drugsmentioning
confidence: 96%
“…Combination of silibinin with phospholipids appears to increase its bioavailability [101]. Several clinical studies evidence the efficacy of silibinin combined with phospholipids and vitamin E in patients with NAFLD, who exhibit improvements in aspartate aminotransferase (AST), alanine aminotransferase (ALT) and gamma glutamyl transferase (γGT) levels, insulin resistance and liver histology in addition to the normalization of the cholestasis and cholesterol levels [102][103][104][105].…”
Section: Fig (2)mentioning
confidence: 99%